Pengaruh Kualitas Pelayanan, Promosi, dan Lokasi terhadap Minat Konsumen (Studi Kasus pada Dialer Mataram Sakti Muara Bulian Tahun 2021) - Raden Hebat Kurnia; Wina Sari Asmara; Ratumas Hartha Delima (CITRA EKONOMI, 2022)
In this study, the variables used were service quality, promotion, location and consumer interest in a case study at the Mataram Sakti dealer in Muara Bulian. The purpose of this research is to provide input to the dealers of Mataram Sakti Muara Bulian and increase knowledge for readers. The research method used is by distributing questionnaires to customers who visit the Mataram Sakti Muara Bulian dealer, in answering the questionnaire respondents simply mark the column that has a Likert's Scale (1 - 5) above it. The results obtained from this study, partially service quality (X1), promo (X2) and location (X3) on consumer interest (Y) have a positive and significant influence both partially and simultaneously, then partially service quality (X1), promo (X2) and location (X3) on consumer interest (Y) have a positive and significant influence both partially and simultaneously,